Stability Analysis and H∞ Model Reduction for Switched Discrete-Time Time-Delay Systems. (26th November 2013) - Liu, Zheng-Fan; Cai, Chen-Xiao; Duan, Wen-Yong
Abstract : This paper is concerned with the problem of exponential stability and H ∞ model reduction of a class of switched discrete-time systems with state time-varying delay. Some subsystems can be unstable. Based on the average dwell time technique and Lyapunov-Krasovskii functional (LKF) approach, sufficient conditions for exponential stability with H ∞ performance of such systems are derived in terms of linear matrix inequalities (LMIs). For the high-order systems, sufficient conditions for the existence of reduced-order model are derived in terms of LMIs. Moreover, the error system is guaranteed to be exponentially stable and an H ∞ error performance is guaranteed. Numerical examples are also given to demonstrate the effectiveness and reduced conservatism of the obtained results.